Autopsy Observations in Lethal Short-Rib Polydactyly Syndromes. (January 2015) - Okiro, Patricia; Wainwright, Helen; Spranger, Jürgen; Beighton, Peter
The short rib-polydactyly syndromes are a heterogeneous group of lethal autosomal recessive disorders (SRP I–IV), which result from cellular ciliary dysfunction during embryogenesis. Diagnosis is conventionally based on radiographic imaging. Since 1976, postmortem investigations of 5 affected fetuses or stillbirths have been undertaken and the visceral abnormalities have been documented. These anomalies are discussed in the context of prenatal differential diagnosis and prognostication following imaging in pregnancy and at autopsy following miscarriage or stillbirth.